Design and Implementation of World Wide Web Pages for the Computational Information Systems Research Group in the Department of Information Studies, University of Sheffield - Rahela, Rahim (1995)
This dissertation consists of six chapters, and describes the design and implementation of the World Wide Web pages for the Computational Information Systems Research Group in the Department of Information Studies. The idea of implementing the World Wide Web pages for the research group is to get the information of the group published on the Internet. The area of networking (Internet) is reviewed particularly with reference to the World Wide Web. A few network tools are discussed. The emphasis is given more on the World Wide Web and the browser used as these form the most important part in this project. The Web pages were created via the HTML editor called the HTML Writer. The HTML language used in writing the program is described together with a brief description of the functions used in the program. A few number of hyper-editing systems are also discussed, with most attention being given to the hyper-editing system used in this project. The comparison was made between HTML Writer and the Hot-Metal Editor. The design and development of the Web pages is described from the first attempts to write the program to the final version. Lastly, the Web pages are reviewed as the final step in completing this project.